Torsion of a rectangular prismatic bar solution using a power fit model - Danao, Louis Angelo M.; Cabrera, Ryan M.
The torsion problem of a rectangular prismatic bar is solved using the Saint Venant's warping function method and analytic solutions to the twisting moment and the non-vanishing shear stresses are presented. Approximate solutions to the torsion problem are derived by curve fitting the analytic solutions using a power fit model with the lengths of the rectangle sides as parameters. Errors observed did not exceed 0.6 percent. The study successfully presents a solution to the maximum non-vanishing shear stress at the narrow side of the rectangular section. Such a solution will be useful for the assessment of the critical points on a section that experiences combined bending and torsion loads.
Keywords: Torsion; Rectangular section; Saint-Venant.; Warping function; Twisting moment; Shear stress